Sexual dimorphism of pelvimetry in children at the circum puberal age: A study of children in lmogiri District Bantu! Regency Yogyakarta Special Provinc - Janatin Hastuti, Janatin Hastuti (Universitas Gadjah Mada, 2004)
Background: Age of circum puberal is important because during this period primary and secondary sexual characteristics are developing. Morphological sexual differentiations of boys and girls during this period cause sexual dimorphism, i.e. anatomical differences especially in the body measurements. One of the important variations is the measurements of pelvic (pelvimetry).Objective: The aims of this studi were to know the pelvimetric sexual dimorphism of boys and girls at the circum puberal age.Methods: Investigation was conducted on 172 children of 12 up to 15 years old which consisted of 72 boys and 100 girls who were born and lived in Imogiri District, Bantu! Regency, Yogyakarta Special Province.The samples were divided into 4 groups and were measured on height, weight, bicristal breadth, biiliospinal anterior breadth, bitrochanteric breadth, distance of lumbale-symphysion and pelvic girdle. The indices calculated are Livis index, bicristal index, bitrochanteric index, and the sexual dimorphism index of all measurements. The datas were analysed using two-ways anova, student-t analysis, and Kolmogorov-Smirnov test.Results: The result showed that bicristal breadth, biiliospinal anterior breadth and distance of lumbalesymphysion did not indicate sexual dimorphism significantly in children in the circum puberal age, although girls at 12 and 13 years old have greater measurements than boys. Bitrochanteric breadth and pelvic girdle showed sexual dimorphism since the age of 13 years, girls had greater measurements than boys. Sexual dimorphism of pelvic shape showed by bicristal index was happened at 15 years old, girls had greater index than boys. Sexual dimorphism of hip shape showed by bitrochanteric breadth index was happened since 13 years old, girls had greater index than boys.Conclusions: It was concluded that pelvic measurements showed sexual dimorphism in children at the circum puberal age by different time and pattern.Key words: sexual dimorphism - pelvimetry - children - circum puberal